2011
DOI: 10.1073/pnas.1106880108
|View full text |Cite
|
Sign up to set email alerts
|

Endonuclease VIII-like 3 (Neil3) DNA glycosylase promotes neurogenesis induced by hypoxia-ischemia

Abstract: Neural stem/progenitor cell proliferation and differentiation are required to replace damaged neurons and regain brain function after hypoxic-ischemic events. DNA base lesions accumulating during hypoxic-ischemic stress are removed by DNA glycosylases in the base-excision repair pathway to prevent cytotoxicity and mutagenesis. Expression of the DNA glycosylase endonuclease VIII-like 3 (Neil3) is confined to regenerative subregions in the embryonic and perinatal brains. Here we show profound neuropathology in N… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

12
127
1

Year Published

2013
2013
2018
2018

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 82 publications
(141 citation statements)
references
References 53 publications
12
127
1
Order By: Relevance
“…Hypoxia during ischemia has also been shown to induce neuronal pathology in Neil3 2/2 mice, that display reduced microglial content and a significant loss of neuronal progenitors specifically in the striatum during hypoxic injury [Sejersted et al, 2011]. Furthermore, neural stem/ progenitor cells from aged Neil3 2/2 mice were reported to have reduced proliferative capacity and reduced DNA repair activity, corresponding with learning and memory deficits observed in aged Neil3 2/2 mice [Regnell et al, 2012].…”
Section: Neurodegenerationmentioning
confidence: 99%
“…Hypoxia during ischemia has also been shown to induce neuronal pathology in Neil3 2/2 mice, that display reduced microglial content and a significant loss of neuronal progenitors specifically in the striatum during hypoxic injury [Sejersted et al, 2011]. Furthermore, neural stem/ progenitor cells from aged Neil3 2/2 mice were reported to have reduced proliferative capacity and reduced DNA repair activity, corresponding with learning and memory deficits observed in aged Neil3 2/2 mice [Regnell et al, 2012].…”
Section: Neurodegenerationmentioning
confidence: 99%
“…Since we aimed for a milder oxidative insult, proliferation of microglia increased in a more modest manner as compared with HI in the immature brain (28). Astrocytes are affected by microglia activation after HI, contributing to excessive release of inflammatory mediators which can further intensify the injury (5).…”
Section: Gene Expression In the Newborn Brainmentioning
confidence: 99%
“…To determine apoptosis and/or necrosis, a pathologist blinded to the experimental groups assessed hematoxylin and eosin-stained brains in the regions of interest: hippocampus, cortex, and striatum. Immunostaining was performed as previously described (28). The primary antibodies and dilutions used were mouse anti-GFAP 1:400 (G3893; Sigma, St.Louis, MO) and rabbit anti-Iba1 1:2000 (019-19741, Wako, Richmond, VA).…”
Section: Gene Expression In the Newborn Brainmentioning
confidence: 99%
“…NEIL3 expression has also been detected in regions rich in neurogenesis in the embryonic brain [28] and in two recent studies NEIL3-null models showed a decreased differentiation potential of neural stem cells. [29,30] NEIL3-null mice showed learning and memory deficits and reduced anxiety-like behavior, and synaptic irregularities in hippocampal neurons. [31] All together, these results suggest that NEIL3 may have a specific role in neurogenesis in the central nervous system.…”
Section: Neil3 Expression Patternsmentioning
confidence: 99%
“…[36] In order to understand the relationship between NEIL3 and hypoxia-ischemia, Sejersted et al [29] carried out an experiment on NEIL3 gene knockout (NEIL3-null) mice in vitro and in vivo. Interestingly, after hypoxia-ischemia, there is no increase of cellular damage or death in vivo in NEIL3-null mice at an early stage, but a significant deficient in reconstituted neuronal tissue after 42 d. NEIL3-null neurospheres exhibited poor growth and skewed differentiation that could explain the poor outcome of NEIL3-null mice after hypoxic ischemia.…”
Section: Neil3mentioning
confidence: 99%